2022
DOI: 10.1073/pnas.2117323119
|View full text |Cite
|
Sign up to set email alerts
|

Network modeling predicts personalized gene expression and drug responses in valve myofibroblasts cultured with patient sera

Abstract: Aortic valve stenosis (AVS) patients experience pathogenic valve leaflet stiffening due to excessive extracellular matrix (ECM) remodeling. Numerous microenvironmental cues influence pathogenic expression of ECM remodeling genes in tissue-resident valvular myofibroblasts, and the regulation of complex myofibroblast signaling networks depends on patient-specific extracellular factors. Here, we combined a manually curated myofibroblast signaling network with a data-driven transcription factor network to predict … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…Thus, it is suggested that inhibition targeting ferroptosis may be a possible strategy for regression of CAVD. In this study, ferroptosis ( Figure 2F ), ROS metabolic process ( Figures 3A,B ), and NAFLD (containing IL-6, BID, PRKAA2) signaling were identified as the activated biological processes or pathways involved in CAVD, and particularly, NAFLD was validated by WebGestalt, DAVID, and Metascape, which was consistent with the previous findings ( 6 , 21 ). Iron overload was observed in patients with NAFLD and the liver damage could be attenuated by iron removal ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it is suggested that inhibition targeting ferroptosis may be a possible strategy for regression of CAVD. In this study, ferroptosis ( Figure 2F ), ROS metabolic process ( Figures 3A,B ), and NAFLD (containing IL-6, BID, PRKAA2) signaling were identified as the activated biological processes or pathways involved in CAVD, and particularly, NAFLD was validated by WebGestalt, DAVID, and Metascape, which was consistent with the previous findings ( 6 , 21 ). Iron overload was observed in patients with NAFLD and the liver damage could be attenuated by iron removal ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 91%
“…In the future, exploring the combinatorial effects of annexin A2 and cystatin C on fibrosis and calcification in AVS may be fruitful, given the complete proteome in patient sera elicits patient-specific effects on myofibroblast activation. 21,48 Additionally, although porcine VICs are known to respond similarly to human VICs when treated with biochemical factors, 49 reproducing key experiments using human VICs would further enhance the clinical relevance of our findings. We further showed that annexin A2 and cystatin C modulate sex-specific VIC myofibroblast activation through p38 MAPK signaling.…”
Section: Papermentioning
confidence: 75%
“…51 VIC signaling networks are complex and predicting their effects on regulating the transitions from a quiescent fibroblast to myofibroblast or osteoblast-like phenotype remains an ongoing area of research. 48 Previous work has suggested that pro-inflammatory secreted factors mediate a quiescent VIC to myofibroblast transition, followed by proliferation, then termination in an osteoblast-like phenotype. 16 Our data suggest that annexin A2 and cystatin C increase both myofibroblast and osteoblast-like phenotypes.…”
Section: Papermentioning
confidence: 99%
“…Research shows that genetic differences between males and females can also contribute to cardiovascular disease presentation and severity (70,71). Future studies could address this by integrating genomic or transcriptomic data into the model to account for additional differences due to biological sex in addition to gonadal hormones (72).…”
Section: Discussionmentioning
confidence: 99%